CONCEPTUAL RESEARCH ON THE BUSINESS IMPLICATIONS OF COVID-19 IN SABAH USING INDUSTRY ANALYSIS TOOLS - Datu Razali Datu Eranza; Jabil Mapjabil; Andy Lee Chen Hiung; Arsiah Bahron; Hasnah Tanalol (Journal of Islamic, Social, Economics and Development, 2020)
COVID-19 Pandemic undoubtedly gives huge impacts to business organizationespecially in Sabah tourism industry. The outbreak has led to the resort of lay-off of workforce,retrenchment of staff, and downsizing of business. To sustain, organizations must formulatestrategy to deal with the recession whilst in the meantime, there is a need of research to conductstudy on the impacts of the pandemic and with such results can be used for government toformulate better intervention plan and strategic planning. This paper consists of backgroundof study, problem statement, research questions and objectives, and research design. From thediscussion, it is generalized that few trends are suggested by global consultant companies, andthere is a need to conduct industry analysis as response to that. Interviews and questionnaireare proposed to be used to conduct industry analysis tools using Porter’s five forces model andbroad factor analysis.